2014
DOI: 10.1111/hex.12259
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in the communication needs of adolescents with psychosocial problems and their parents

Abstract: Background In patient-centred care, professionals should recognize their patient's needs and adapt their communication accordingly. Studies into patients' communication needs suggest priorities vary depending on sociodemographic characteristics, and type and severity of the complaints. However, evidence lacks on priorities in the communication needs of adolescents in psychosocial care and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This stresses the importance placed on this aspect by clients in psychosocial care [23], which also holds true for other care settings [24,25]. Our study provides empirical evidence for the assumption that fostering a relationship is important in order to accomplish a productive care process in psychosocial care for children and adolescents [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 55%
“…This stresses the importance placed on this aspect by clients in psychosocial care [23], which also holds true for other care settings [24,25]. Our study provides empirical evidence for the assumption that fostering a relationship is important in order to accomplish a productive care process in psychosocial care for children and adolescents [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 55%
“…This was unexpected because affective quality of the communication is considered by adolescents in psychosocial care to be the most important communication domain [33], and these needs are often not met [18]. A reason for our finding may be that affective quality has its highest impact on outcomes in the first stage of the care process.…”
Section: Discussionmentioning
confidence: 89%
“…Although patient-centered communication may have a positive effect on health outcomes, evidence as to these associations is very limited [31, 32]. One reason may be that most studies adopt a ‘one way fits all’ approach that fails to take individual patients’ needs into account, whereas we know that not all patients want the same thing [33]. This study used a tailoring approach in measuring patient-centered communication by combining patients’ attributed relevance to communication at the start of treatment and their actual communication experiences during treatment; this may explain our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have shown that families who had good, collaborative relationship with the care provider were more likely to be willing to engage in the treatment and remain longer in it ( Hawley and Weisz, 2005 ; Flicker et al, 2008 ). Adding to that, Nobile and Drotar (2003) showed that effective parent-provider communication was associated with parental satisfaction, and adherence to treatment and communication was perceived as the most important factor of care for both parents and adolescents ( Jager et al, 2015 ). Parental training may help to reach better parent-adolescent relationships ( Ozturk et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%